ADAPTIVE COVARIANCE STABILIZATION OF VIDEO IMAGE - I. A. Baryskievic; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An adaptive method of video image stabilization is proposed. It is based on gradient covariance features and selective search for best matching. The comparison of proposed adaptive covariance and known SURF methods is provided.